2011
DOI: 10.1074/jbc.m110.217380
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent Impairment of Intracellular Apolipoprotein E4 Trafficking and Its Detrimental Effects Are Rescued by Small-molecule Structure Correctors

Abstract: Apolipoprotein (apo) E4 is the major genetic risk factor for Alzheimer disease (AD) and likely contributes to neuropathology through various pathways. Here we report that the intracellular trafficking of apoE4 is impaired in Neuro-2a cells and primary neurons, as shown by measuring fluorescence recovery after photobleaching. In Neuro-2a cells, more apoE4 than apoE3 molecules remained immobilized in the endoplasmic reticulum (ER) and the Golgi apparatus, and the lateral motility of apoE4 was significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 55 publications
4
99
0
1
Order By: Relevance
“…Previously, we demonstrated that the intracellular trafficking of apoE4 is impaired in the endoplasmic reticulum and Golgi apparatus of Neuro-2a cells expressing apoE4 compared with apoE3 trafficking, as determined by fluorescence recovery after photobleaching (24). ApoE4-R61T, which lacks domain interaction, gave results comparable with those for apoE3.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…Previously, we demonstrated that the intracellular trafficking of apoE4 is impaired in the endoplasmic reticulum and Golgi apparatus of Neuro-2a cells expressing apoE4 compared with apoE3 trafficking, as determined by fluorescence recovery after photobleaching (24). ApoE4-R61T, which lacks domain interaction, gave results comparable with those for apoE3.…”
Section: Discussionmentioning
confidence: 49%
“…domain interaction between Arg-61 and Glu-255) markedly alters its structure and accounts for many of the functional features that distinguish apoE4 from apoE3 (6,8,9,12,13). The neuropathological features of apoE4 include (a) impaired neurite outgrowth (17)(18)(19); (b) disruption of the cytoskeleton in neurons (38), including increased Tau hyperphosphorylation (39,40); (c) mitochondrial dysfunction in neurons, including altered mitochondrial membrane potential (36) and decreased respiratory enzyme levels and activity (16); (d) impaired neuronal mitochondrial motility (current study); (e) impaired synaptogenesis (20,24); (f) enhanced susceptibility to neuron-specific proteolysis and neurotoxic fragment formation (39 -41), (g) increased amyloid ␤ production (21); (h) increased neuronal lysosomal leakage and apoptosis (42); (i) CNS neuropathology and impaired behavioral activity (26,27,41,43), and (j) enhanced amyloid ␤ deposition (44 -47). All of these abnormal features (a through i above) that distinguish apoE4 from apoE3 are corrected or significantly improved by blocking apoE4 domain interaction by mutation of Arg-61 to threonine, small molecule structure correctors, or engineering of mouse apoE to alter domain interaction (8 -11, 24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations